2013
DOI: 10.4314/thrb.v15i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to delay in commencement of immunization in Nigerian infants

Abstract: Delay in receipt of immunisation may result in a child being susceptible to vaccine preventable diseases for prolonged periods. Identification of factors which contribute to delay in receipt of immunisation will help in developing targeted interventions. This study examined prospectively factors contributing to delay in the commencement of infant immunisation in Benin City, Nigeria. This was a cross-sectional descriptive study of 153 consecutive mothers of infants presenting for their first immunisation at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
(27 reference statements)
9
26
2
Order By: Relevance
“…Studies were conducted in populations in India ( n  = 23) [7, 9, 3858], Pakistan ( n  = 3) [59–61], Iran ( n  = 1) [62], China ( n  = 1) [63], Kenya ( n  = 6) [10, 6468], Nigeria ( n  = 4) [8, 6971], Burkina Faso ( n  = 1) [10], Ethiopia ( n  = 1) [72], Democratic Republic of Congo (DRC)( n  = 1) [37], Central African Republic (CAR)( n  = 1) [73], Zambia ( n  = 1) [74], and Brazil ( n  = 2) [75, 76],…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in populations in India ( n  = 23) [7, 9, 3858], Pakistan ( n  = 3) [59–61], Iran ( n  = 1) [62], China ( n  = 1) [63], Kenya ( n  = 6) [10, 6468], Nigeria ( n  = 4) [8, 6971], Burkina Faso ( n  = 1) [10], Ethiopia ( n  = 1) [72], Democratic Republic of Congo (DRC)( n  = 1) [37], Central African Republic (CAR)( n  = 1) [73], Zambia ( n  = 1) [74], and Brazil ( n  = 2) [75, 76],…”
Section: Resultsmentioning
confidence: 99%
“…In two studies conducted in Pakistan, maternal knowledge of immunization was an important factor; [61] and the reasons for under-immunization given by mothers were to do with ‘carelessness’ or difficulty in accessing services [60]. In Ibadan, Nigeria, a study found fear of side-effects, maternal awareness, and parents being too busy to attend clinic to be significant; [8] in neonates in Benin City, Nigeria, a study found that SE and education status were associated with delayed immunization; [69] and the 3 main reasons for under-vaccination identified in a study from Bangui, Central African Republic, were the mother being too busy, negative attitude of health workers, and lack of access to information [73]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were observed by Sadoh AE et al where on time vaccinations for class I, class II, class III and class IV were 75%, 52%, 50% and 25%, respectively and the difference was significant. (20) In this study, working mothers made more delayed vaccinations (67.6%) for their babies as compared to housemakers (60.5%). A study conducted by Rahji F R et al found that housewives got significantly less compliance in immunisation than working mothers.…”
Section: Discussionmentioning
confidence: 56%
“…Similar findings were observed by Sadoh AE et al conducted a study on Nigerian infants and Luman ET et al where education played one important role for timeliness of vaccination. (20), (9) Mothers with higher education group got more timely vaccination of babies as compared to lower education group.…”
Section: Discussionmentioning
confidence: 99%